Democratic Republic of Timor-Leste : Public Financial Management-Performance Report. (IMF Staff Country Reports; Country Report, 2010)
Timor-Leste weathered the global financial crisis well and experienced healthy economic growth rates. It has made solid progress in strengthening the public financial management systems. The budget document provides comprehensive information; fiscal transparency is high. The Ministry of Finance lacks the time and capacity for adequate review of rationale, costing, and impact of public investment. Internal and external audit form the largest gaps in the present public financial management system. Buy-in and long-term commitment from development partners will be essential.